Upper thermal tolerance of closely related Danio species. Issue 4 (April 2014) - Sidhu, R.; Anttila, K.; Farrell, A. P.
<x xml:space="preserve">Abstract</x> The main finding of this study was that measuring maximum heart rate during incremental warming was an effective tool to estimate upper thermal limits in three small cyprinid Danio species, which differed significantly. Arrhenius breakpoint temperature for maximum heart rate, purportedly an index of optimum temperature, was 21·2 ± 0·4, 20·1 ± 0·4 and 18·9 ± 0·8° C (mean ± s.e.) for zebrafish Danio rerio, pearl danio Danio albolineatus and glowlight danio Danio choprae, respectively. The temperature where cardiac arrhythmias were first induced during warming (Tarr) was 36·6 ± 0·7, 36·9 ± 0·8 and 33·2 ± 0·8° C (mean ± s.e.) and critical thermal maximum (TCm) was 39·9 ± 0·1, 38·9 ± 0·1 and 37·2 ± 0·1° C (mean ± s.e.) for D. rerio, D. albolineatus and D. choprae, respectively. The finding that Tarr was consistently 3–4° C lower than TCm suggests that collapse of the cardiac life support system may be a critical trigger for upper temperature tolerance. The upper thermal limits established here, which correlate well with a broad natural environmental temperature range for D. rerio and a narrow one for D. choprae, suggest that upper thermal tolerance may be a genetic trait even among closely related species acclimated to common temperatures.